Moderating effects of consumer corporate identification on purchase intention predictors for local brand automobiles in Abuja, Nigeria and the Klang Valley, Malaysia - Chinedu, Anyanwu Hilary (2021)
Changes in consumers’ product evaluation criteria in the past decade have necessitated consumers’ adoption of mechanisms that reflect their values and benefit them via purchase decisions. This exposed the lacuna in consumer research on the lack of a viable business model that ensures consumers’ interests and values are simultaneously actualized alongside purchase intention for local products as a means of sustaining consumers’ well-being, beliefs, and local economic growth in developing countries. Building on the theories of planned behavior (TPB), social identity, and Hofstede’s cultural value model, the study compared the moderating effects of consumer corporate identification (CCI) on the predictors of purchase intention for a local brand automobile manufactured in Nigeria and Malaysia respectively. Predicated on a positivist epistemological approach, questionnaires were distributed to potential consumers of Innoson vehicle manufacturing (IVM) in Abuja, Nigeria, and potential consumers of Proton automobiles in Klang Valley, Malaysia through a mall intercept survey. About 99% and 97% usable responses were collected from the Nigerian and Malaysian respondents respectively. Data were analyzed using IBM SPSS version 25 and Amos version 24. Pooled confirmatory factor analyses revealed that Proton model demonstrated a slightly better fit indices compared to IVM model. However, both models achieved the required fit indices. IVM respondents consisted of 51.6% males and 48.4% females with an age mean of 33.67, while Proton respondents involved 51.5% females and 48.5% males with an age mean of 30.94. IVM potential consumers exhibited high/positive (above 50%) levels on all the study constructs. Apart from consumer ethnocentrism, Proton potential consumers demonstrated high/positive (above 50%) levels on other constructs of the study. Results of t-test revealed no significant mean difference in purchase intention across gender in both datasets. Structural equation modeling (SEM) showed that consumer ethnocentrism and collectivism explained a higher variance (43.7%) in attitude towards purchase intention for local brand automobiles in Proton model than IVM model (33.6%). Consumer ethnocentrism and collectivism significantly influenced attitude towards purchase intention for local brand automobiles in Proton model, whereas only consumer ethnocentrism significantly influenced attitude towards purchase intention for local brand automobiles in IVM model. SEM further revealed that attitude, subjective norm (SN), and perceived behavioral control (PBC) explained higher variance (60.3%) in purchase intention for local brand automobiles in IVM model compared to Proton model (57.5%). While attitude, SN, and PBC significantly predicted purchase intention in Proton model, only attitude and PBC significantly predicted purchase intention in IVM model. Lastly, multiple group analyses (MGA) indicated that CCI moderated the current research model. CCI significantly moderated only the predictive effects of PBC on purchase intention for local brand automobiles in Abuja and Klang Valley. The study concluded that positive attitude towards purchase intention for local products are unlikely without consumer ethnocentrism irrespective of consumers’ collectivistic tendencies. Bearing in mind the efficacy of TPB in underpinning purchase intention and the predictive effects of attitude, SN, and PBC on purchase intention, behavioral controls to automobile purchase intention is decimated or reversed in the face of CCI engagements. Theoretical and practical implications are discussed.